A Transient Dynamic Model of Brake Corner and Subsystems for Brake Creep Groan Analysis - Dejian Meng; Lijun Zhang; Jie Xu; Zhuoping Yu (Shock and Vibration)
To improve the understanding of brake creep groan, both experimental and numerical studies are conducted in this paper. Based on a vehicle road test under the condition of downhill, complicated stick-slip type motion of caliper and its correlation with the interior noise were analyzed. In order to duplicate these brake creep groan phenomena, a transient dynamic model including brake corner and subsystems was established using finite element method. In the model, brake components were considered to be flexible body, and the subsystems including driveline, suspension, tire, and vehicle body were considered to be rigid body. Simulation and experimental results of caliper vibration in time and frequency domains were compared. It was demonstrated that the new model is effective for the prediction and analysis of brake creep groan, and it has higher accuracy compared to the previous model without the subsystems. It is also found that the lining and caliper not only have stick-slip motion in each coordinate direction but also have translational and torsional movements in plane, which relate to the microscopic sticking and slipping, friction coefficient, and forces, as well as the contact status at the friction interface.